Hubungan Pola Makan, Aktifitas Fisik dan Media Informasi dengan Status Gizi Remaja: Relationship between Diet, Physical Activity and Information Media with Nutritional Status of Adolescents - Merlin Farlina; Istiana Kusumastuti; Catur Septiawan (Jurnal Interprofesi Kesehatan Indonesia, 2022)
Background: Nutritional problems at this time are still one of the very concerning health problems, nutritional problems can be found in developing countries, one of which is Indonesia. Objectives: This study aimed to determine the relationship between diet, physical activity, and information media with the nutritional status of adolescents at MA Nida Bahari Jampangkulon in 2021. Method: This type of research used quantitative research, using a cross-sectional approach with analytical descriptive methods. The research population was all adolescents in MA Nida Bahari Jampangkulon, totaling 138 students and the research sample had as many as 58 respondents using the Random Sampling technique. The data was obtained from the Chi-Square test using SPSS. Results: The results showed that there was a relationship between diet and nutritional status, p-value = 0.021 with an OR value of 4.073 (1,366-12,143), physical activity with nutritional status, p-value = 0.003 with an OR value of 6,139 (1,980-19036) and information media with nutritional status p-value. = 0.002 with an OR value of 6.429 (2.056-20.104). Conclusion: This study concludes that there is a relationship between diet, physical activity, and information media with the nutritional status of adolescents at MA Nida Bahari Jampangkulon in 2021.